Digital case-based learning of ecosystem (DEco) for form 2 students - Man, Suhaini Che; Azid, Nurulwahida; Shuib, Robiah; Yahya, Furiza; Nelliraharti, Nelliraharti (AIP conference proceedings, 2023)
Inculcating awareness in preserving and protecting the environment among citizens is crucial. Thus, effort of doing so is to be carried out especially among young generations. Digital Case-based Learning of Ecosystem (DEco) is an interactive tool, designed mainly to help students to better understand the topic of ecosystem and more importantly to instill environmental awareness amongst form 2 students. This application is developed based on case-based learning, by introducing cases as a problem to be clarified and addressed through a sequence of investigation tasks. DEco is also equipped with Web 2.0 tools to enhance students’ engagement throughout the learning session. Seven experts in science subject and in Information and Communication Technology (ICT) with more than ten years of experience, were appointed to evaluate this interactive application. An Intra-class Correlation Coefficient (ICC) was used, to estimate expert’s agreement on this interactive tool. The finding revealed a value for average measure was .992, that was a high degree of expert’s evaluation consensus for Digital Case-based Learning of Ecosystem (DEco) in terms of its design and curriculum.